2022
DOI: 10.1002/ehf2.13725
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001206 regulates miR‐665/CRKL axis to alleviate hypoxia/reoxygenation‐induced cardiomyocyte injury in myocardial infarction

Abstract: Aims Myocardial infarction (MI) is a type of cardiovascular disease caused by myocardial necrosis. Growing evidences have suggested that circular RNAs (circRNAs) play crucial roles in cardiac hypoxia/reoxygenation (H/R)-induced injury of MI. Methods and resultsHypoxia/reoxygenation model of H9C2 cells was established and circ_0001206 expression was detected via quantitative real-time polymerase chain reaction. Ribonuclease R (RNase R) and Actinomycin D (Act D) assays verified the stability. Cell counting kit-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In H/R-treated CMs, circ_0001206 overexpression enhanced cell viability and suppressed apoptosis. The results suggested the cardioprotective role of circ_0001206 ( Wang et al, 2022 ). Circ_0001206 could bind to miR-665, which was validated to target CRKL.…”
Section: Circrnas and MImentioning
confidence: 87%
See 3 more Smart Citations
“…In H/R-treated CMs, circ_0001206 overexpression enhanced cell viability and suppressed apoptosis. The results suggested the cardioprotective role of circ_0001206 ( Wang et al, 2022 ). Circ_0001206 could bind to miR-665, which was validated to target CRKL.…”
Section: Circrnas and MImentioning
confidence: 87%
“…CRK like proto-oncogene, adaptor protein (CRKL) has been found to mitigate CM injury induced by hypoxia/reoxygenation (H/R) in MI ( Zhang et al, 2015 ). In this study, H/R treatment was used to construct an in vitro MI model ( Wang et al, 2022 ). Wang et al found a circRNA produced by the CRKL gene, circ_0001206 ( Wang et al (2022) .…”
Section: Circrnas and MImentioning
confidence: 99%
See 2 more Smart Citations
“…Circular RNAs are distributed extensively throughout the cardiovascular system and vary dramatically in their expression levels in the context of different cardiac disorders, such as acute MI, angina pectoris, and myocarditis, and function as regulators of heart development, cardiac function, and stress response. Plenty of research has indicated that the critical features of circular RNAs are related to MI [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. These circRNAs with altered levels have been found to regulate cardiac cell death after the onset of MI, such as apoptosis, autophagy, necrosis, and inflammatory infiltration, and also regulate myocardial collagen deposition and fibrosis during the healing stage of MI.…”
Section: Conclusion On the Specific Functions Of Circular Rnas In Myo...mentioning
confidence: 99%